CHILDHOOD OBESITY AND ITS RISK FACTORS: A REVIEW ARTICLE - Gogoi, Nirmali; Nath, Ishita (International Journal of Psychosocial Rehabilitation, 2021)
Obesity is a complex issue that affects children across all age groups. Childhood obesity has become a major global epidemic that imposes a substantial social and health burden worldwide. An estimated 4.0 million deaths and 120 million disability-adjusted life years (DALYs) in 2015 were attributable to an excess body mass index (BMI) globally. The global estimation by WHO showed that, in 2019, an estimated 38.2 million children under the age of 5 years were overweight or obese. A CDC report from 2017-2018 revealed that the prevalence of obesity was 19.3% and affected about 14.4 million children and adolescents. Obesity prevalence was 13.4% among 2 to 5-year-olds, 20.3% among 6 to 11-year-olds, and 21.2% among 12 to 19-year-olds. Some studies have found that BMI is 25-40% heritable. The genetic factor accounts for less than 5% of cases of childhood obesity. Dietary factors such as fast food consumption, sugary beverages, snack foods, portion size, and skipping breakfasts have been studied extensively for their possible contributions to the rising rates of childhood obesity. Each additional hour of television per day increased the prevalence of obesity by 2%. Studies have shown that having an overweight mother and living in a single-parent household are associated with overweight and childhood obesity. In India, while the country is still struggling with the burden of malnutrition, the issue of over-nutrition cannot be ignored. India should also formulate a national policy and partner with the private sector to address the childhood obesity epidemic.